Multifaceted CA@TiO2 nanocomposite-based thin film composite membrane for advanced separation and environmental detoxification - Mohd Arsalan; Rhithuparna D.; Mohd Adeel Khan; Wasi Ur Rahman; Mohamed Fahad Alajmi; Afzal Hussain; Bon-Heun Koo; Gopinath Halder (Next Materials, 2025)
Reverse osmosis (RO) membranes play a pivotal role in modern potable water reuse systems, providing an effective barrier against dissolved organic compounds, salts, and harmful pathogens. In this study, the synthesis, fabrication, and performance evaluation of a cellulose acetate blended titanium oxide (CA@TiO2) composite RO membrane, prepared via the phase-inversion method is reported. The hydrophilic CA polymer served as a binder, while TiO2 nanoparticles, known for their excellent antibacterial properties, were incorporated to enhance membrane durability and water permeability. Dimethylformamide (DMF) was employed as the solvent during membrane casting. Comprehensive characterization of the synthesized membrane was conducted using XRD, FTIR, FESEM, and TGA/DTA analysis. The membrane demonstrated effective removal of desalination ions (Ca2 +, Mg2+) and heavy metal ions (Ni2+, Zn2+, Cd2+, Cr3+, Fe3+), confirming its potential in water treatment applications. The membrane showed over 60 % salt rejection for Ca2+ and Mg2+, and removed 90–97 % of heavy metals like Ni2+, Zn2+, Cd2+, Cr3+, and Fe3+. It achieved about 85 % oil/water separation efficiency and degraded 89.6 % of methylene blue under UV light in 90 min, showing good photocatalytic activity. Overall, the synthesized CA@TiO2 membrane offers promising potential for sustainable water purification and wastewater treatment.